Influence of working gas pulse injection and fluctuations of the magnetic field on the runaway electrons dynamics in Uragan-3M - Tarasov, I.K.; Tarasov, M.I.; Sitnikov, D.A.; Korovin, V.B.; Lozin, A.V.; Shapoval, A.N.; Makhov, M.M.; Mironov, Yu.K.; Romanov, V.S.; Pavlichenko, R.O.; Zamanov, N.V.; Kulaga, A.G.; et al. (Вопросы атомной науки и техники, 2019)
Generation of runaway electrons in fusion experiments can drive to serious damage of plasma devices components. Injection of gas with a large mass number decreases the generation processes. Also, magnetic perturbations decrease generation of runaway electrons by increasing the loss rate. We investigated the influence of working gas pulse injection and natural fluctuations of the magnetic confining field on runaway electrons dynamics. The interaction of runaway electrons with an Alfven wave in plasma is noted. Генерація утікаючих електронів в експериментах синтезу може привести до серйозного пошкодження компонентів плазмових пристроїв. Інжекція важкого газу зменшує процеси генерації. Магнітні збурення також пригнічують генерацію утікаючих електронів за рахунок збільшення швидкості втрат. Досліджено вплив імпульсного напуску газу і природних флуктуацій утримуючого магнітного поля на динаміку утікаючих електронів. Відзначено взаємодія утікаючих електронів з альфвеновською хвилею в плазмі. Генерация убегающих электронов в экспериментах синтеза может привести к серьезному повреждению компонентов плазменных устройств. Инжекция тяжелого газа уменьшает процессы генерации. Магнитные возмущения также подавляют генерацию убегающих электронов за счет увеличения скорости потерь. Исследовалось влияние импульсного напускающего газа и естественных флуктуаций удерживающего магнитного поля на динамику убегающих электронов. Отмечено взаимодействие убегающих электронов с альфвеновской волной в плазме.